BAG6 negatively regulates the RLR signaling pathway by targeting VISA/MAVS - Huang, Jing-Ping; Li, Jing; Xiao, Yan-Ping; Xu, Liang-Guo (Frontiers in Immunology, 2022)
The virus-induced signaling adaptor protein VISA (also known as MAVS, ISP-1, Cardif) is a critical adaptor protein in the innate immune response to RNA virus infection. Upon viral infection, VISA self-aggregates to form a sizeable prion-like complex and recruits downstream signal components for signal transduction. Here, we discover that BAG6 (BCL2-associated athanogene 6, formerly BAT3 or Scythe) is an essential negative regulator in the RIG-I-like receptor signaling pathway. BAG6 inhibits the aggregation of VISA by promoting the K48-linked ubiquitination and specifically attenuates the recruitment of TRAF2 by VISA to inhibit RLR signaling. The aggregation of VISA and the interaction of VISA and TRAF2 are enhanced in BAG6-deficient cell lines after viral infection, resulting in the enhanced transcription level of downstream antiviral genes. Our research shows that BAG6 is a critical regulating factor in RIG-I/VISA-mediated innate immune response by targeting VISA.